2019
DOI: 10.3390/v11020136
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity and Efficacy of a Novel Multi-Antigenic Peptide Vaccine Based on Cross-Reactivity between Feline and Human Immunodeficiency Viruses

Abstract: For the development of an effective HIV-1 vaccine, evolutionarily conserved epitopes between feline and human immunodeficiency viruses (FIV and HIV-1) were determined by analyzing overlapping peptides from retroviral genomes that induced both anti-FIV/HIV T cell-immunity in the peripheral blood mononuclear cells from the FIV-vaccinated cats and the HIV-infected humans. The conserved T-cell epitopes on p24 and reverse transcriptase were selected based on their robust FIV/HIV-specific CD8+ cytotoxic T lymphocyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…Increases in CD4 + and CD8 + T cell MAP responses were observed in nearly 80% of the cats, implying protection against FIV [41]. This criterion can be similarly applied in humans to select for protective HIV-1 peptides that can be used to formulate an effective vaccine against HIV-1.…”
Section: Hiv Vaccine Candidates and Antibodies Expressed In Plantsmentioning
confidence: 98%
See 1 more Smart Citation
“…Increases in CD4 + and CD8 + T cell MAP responses were observed in nearly 80% of the cats, implying protection against FIV [41]. This criterion can be similarly applied in humans to select for protective HIV-1 peptides that can be used to formulate an effective vaccine against HIV-1.…”
Section: Hiv Vaccine Candidates and Antibodies Expressed In Plantsmentioning
confidence: 98%
“…Recently, evolutionarily conserved epitopes between Feline immunodeficiency virus (FIV) and HIV were explored as a means of developing an effective vaccine [41]. In this study, Sahay and colleagues identified overlapping peptides that elicited T cell immunity in HIV-infected people and FIV-vaccinated cats.…”
Section: Hiv Vaccine Candidates and Antibodies Expressed In Plantsmentioning
confidence: 99%
“…2 ) (Tam 1988 ). Synthesizing peptides as MAP and peptide dendrimers can induce higher immune response and recently were used as a vaccine model against Plasmodium falciparum (Mahajan et al 2010 ), Yersinia pestis (Shreewastav et al 2012 ), filarial nematodes (Immanuel et al 2017 ), and human immunodeficiency viruses (HIV) (Sahay et al 2019 ). Besides, all required protective B and T cell epitopes can be included in one single MAP molecule (Fig.…”
Section: Vaccine Candidates In Experimental Trialsmentioning
confidence: 99%
“…The branched peptides sometimes can greatly increase their immunological responses because of the high molar ratio of peptide antigen to the core molecule and the high molecular weight which make them more immunogenic without the need of conjugation to a carrier protein [32,[34][35][36]. MAP vaccines have been studied in several infectious diseases, such as lymphatic filariasis [37], Plasmodium falciparum (P. falciparum) [38], Yersinia pestis [39], and HIV [40]. Clinical studies have been carried out in MAP vaccine against P. falciparum sporozoites [41].…”
Section: Journal Of Immunology Researchmentioning
confidence: 99%